Social Network Analysis (SNA) on #Kristengray Hashtag: Understanding Gentrification Side Effects Behind the Digital Nomad Phenomenon - Mohammad Thoriq Bahri; Derajad Sulistyo Widhyharto (Jurnal Studi Pemuda, 2021)
Indonesia is one of the destinations countries for digital nomads in South East Asia. Digital Nomad can be described by the person who combining work and leisure activities, without geographical border. The digital nomad lifestyle is becoming trends after an American tourist, Kristen Gray becoming viral on the Twitter Platform, she promoting Bali as a heaven for the digital nomad because of the low cost of living and cultural openness by selling eBook and open consultation services for the people who live in the America and European continents, but then she deported by the Indonesian Immigration Authorities, charged with the misuse of visas (she was used tourism visa for business purposes). Then, the research question arises, Are there potential gentrification effects of digital nomad lifestyle to the local people? And what the government should do to tackle this issue? This research is conducted by analyzing tweets using #kristengray and #digitalnomad hashtag, obtained from 12 January to 12 March 2021. The results are more than 49 percent of users, which dominated by the foreigner is defending Kristen Gray, and forcing the Indonesian Government to open Bali as digital nomad living places, but 51 percent of users, who dominated by Indonesian is refusing what the Kristen Gray doing, by arguing if Bali is purely just for tourism places. The results are the gentrification potentially happening between the digital nomad and local people, because of the difference in economic level, culture and value. Then, the government should consider making a policy to minimize the effects of gentrification resulted in digital nomad activities, suggested opening special visas with the restriction and tax policy for the digital nomad.